Estratégia em produtos culturais: estudo de caso de empresa ex-estatal do setor de telecomunicações - Gangemi, Pedro Paulo de Toledo (2006)
In the 1990, and after the process of privatizations of governmental companies in Brazil, cultural products had gained strategical importance for different types of organizations, specially for nationalized companies of the telecommunications sector. Based on the concept of market orientation, and specifically on the concept of cultural marketing, it is possible to understand the approximation between companies and cultural products restrictedly in the level of products and services. However, there has been little questioning about the concept of market orientation and the marginalization of plural and critical approaches which leaves gaps in the understanding of this approximation. Based in other areas of knowledge which understand this approximation between companies and cultural products and based in studies that present critics about the market forces it is possible to recognize the strategical corporative level of cultural products. Based in specific approaches in strategy, and defending pluralism and interdisciplinary research, it is possible to fill this gaps in the marketing literature. Specifically, in this study, are presented approaches that recognize the dimensions of power, politics and symbolism that influence strategies and are responsible for the approximation between these strategies and cultural products. Especially in Brazil, these debates are central, since in a context composed by nationalized companies many ambiguities are common. With this objective, a case study about a telecommunications sector company that has importance in the investment in cultural products is presented. From this case study, based on primary and secondary data, it is possible to comprehend the strategy in cultural products.